Meningkatkan Aktivitas Belajar melalui Pembelajaran Tematik pada Peserta Didik Kelas I SDN Serangsari - Rigianti, Henry Aditia; Hidayat, Riska Kania (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The problem of this research is the effort to improve students' learning activities through thematic learning in Class I of Serangsari Public Elementary School. The research method is descriptive, the research form is Classroom Action Research (CAR), and it is collaborative. The research subjects are teachers and students of Class I of Serangsari Public Elementary School, totaling 24 people. This research uses direct observation techniques, documentation techniques, and observation sheets as data collection tools. The results of the research based on observations through thematic learning can improve student learning activities. This shows that the hypothesis stating that the implementation of thematic learning in Class 1 of Serangsari Public Elementary School can improve students' learning activities.